TanfÄ«Å¼ TaqwÄ«m Muá¹olÄah FÄ« Å»illi JÄiá¸¥ati Al-WabÄ’ Al-”˜Ä€lami Covid-19 - Munir, Moh. (IAIN Ponorogo, 2022)
Assessment is an essential element in learning activities. Teaching-learning activities need an assessment to measure the learning progress to achieve the objectives. However, the pandemic caused a change in learning activities, leading to changes in the assessment process. This article aims to depict the assessment of the muthola'ah course during the Covid-19 pandemic. Moreover, this article used a qualitative method and employed a case study approach. The analysis in this article used the interactive model of Miles and Huberman. This research was conducted at the Department of Arabic Language Education IAIN Ponorogo. This study indicated that the Taqdim Qissoh in the video was the suitable and effective way to assess muthola'ah material during the Covid-19 pandemic. This method could increase students' enthusiasm for preparing assessment material for Taqdim Qissoh. In addition, this method also eased the other students to understand the muthola'ah material. It also exercised the students’ analysis skills to determine the mistake of the Taqdim Qissoh process so they wouldn’t make the same mistakes later.